2021
DOI: 10.1002/app.50630
|View full text |Cite
|
Sign up to set email alerts
|

Systematic investigation on the effect of crosslinking agent type and dosage on the performance of TPU/MVQ based thermoplastic vulcanizates

Abstract: Dynamic vulcanized thermoplastic polyurethane (TPU)/methyl vinyl silicone rubber (MVQ) thermoplastic vulcanizates (TPVs) were prepared in torque rheometer. The influence of the type and amount of peroxide crosslinking agent on the mechanical properties, thermal stability, micromorphology and melt flowability was systematically investigated. The results showed that the mechanical properties of the TPVs vulcanized by 2,5-dimethyl-2,5-di (tert-butyl peroxy) hexane (DBPH) first increased and then decreased with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…In the final stage of mixing, the torque of all TPVs remained steady after a continuous decline, indicating that the dynamic vulcanization process had been completed and thus presumably the phase inversion occurred, during which the cross-linked HNBR broke up into particles and dispersed in TPEE phase by the shearing action. The torque curve of HNBR/TPEE TPV are coincide with the typical torque variation of dynamically vulcanized TPVs with peroxide cross-linking, 35,36 meaning that the TPVs of this system has successfully achieved dynamic vulcanization.…”
Section: Torque Curves Of Hnbr/tpee Tpv Preparation Processsupporting
confidence: 58%
See 1 more Smart Citation
“…In the final stage of mixing, the torque of all TPVs remained steady after a continuous decline, indicating that the dynamic vulcanization process had been completed and thus presumably the phase inversion occurred, during which the cross-linked HNBR broke up into particles and dispersed in TPEE phase by the shearing action. The torque curve of HNBR/TPEE TPV are coincide with the typical torque variation of dynamically vulcanized TPVs with peroxide cross-linking, 35,36 meaning that the TPVs of this system has successfully achieved dynamic vulcanization.…”
Section: Torque Curves Of Hnbr/tpee Tpv Preparation Processsupporting
confidence: 58%
“…Notably, the enhancement in TS and EB of TPVs after aging is attributed to the further vulcanization of the HNBR under 125°C. During the thermo‐oxidative aging process, the peroxide is further decomposed and slowly released to the extent that the cross‐linking degree of HNBR increases again, achieving a secondary vulcanization of the rubber and resulting in improved mechanical properties of the TPV, as can be corroborated by the aging results of static vulcanized HNBR control samples 1,35 …”
Section: Resultsmentioning
confidence: 69%
“…The integration of mineral particles led to expanding the local free volume in composite structure by improvement in the movement of PU chains. [ 57–60 ] Silane‐treated QRZ and FLS samples gave relatively lower MFI values according to their untreated samples. As an overall conclusion from these results, it can be said that QRZ and FLS additions yielded no indicative problems in the case of processing stages of TPU‐based composites because similar MFI values were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanical properties of TPU/(E) NR blends are often improved by using fillers of natural origin, such as rice husk ash or kenaf fiber [19,20]. In TPU/ methyl vinyl silicone rubber (MVQ) based thermoplastic vulcanizates have shown that both the type and the amount of peroxide used as a vulcanizing agent have a significant effect on the properties of blends [21].…”
Section: Introductionmentioning
confidence: 99%